Monetary integration in the EEC - Dieter Gehrmann (Intereconomics, 1973)
Last weeks' dollar crisis which ended with the devaluation of the dollar emphasised once more the need for a reform of the international monetary system. It also brought to the open the necessity to reorganise the EEC monetary relations. The floating of pound and lira seems to support this case.
Keywords: 330; Monetary Policy